2014
DOI: 10.18632/oncotarget.2654
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of taxol-resistant ovarian cancer cells identifies FKBP5 and the androgen receptor as critical markers of chemotherapeutic response

Abstract: Taxol is a mitotoxin widely used to treat human cancers, including of the breast and ovary. However, taxol resistance (txr) limits treatment efficacy in human patients. To study chemoresistance in ovarian cancer, we established txr ovarian carcinoma cells derived from the SKOV3 cell lineage. The cells obtained were cross-resistant to other mitotoxins such as vincristine while they showed no resistance to the genotoxin cisplatin. Transcriptomic analysis identified 112 highly up-regulated genes in txr cells. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 43 publications
1
59
0
Order By: Relevance
“…B). Furthermore, the effect of phentolamine on paclitaxel resistance was studied through modeling in vitro paclitaxel resistance in SKOV3 cells . The data demonstrated that paclitaxel was 26‐time less potent in inhibiting the proliferation of paclitaxel‐resistant SKOV3 cells (SKOV3/Tx) than that in parent SKOV3 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B). Furthermore, the effect of phentolamine on paclitaxel resistance was studied through modeling in vitro paclitaxel resistance in SKOV3 cells . The data demonstrated that paclitaxel was 26‐time less potent in inhibiting the proliferation of paclitaxel‐resistant SKOV3 cells (SKOV3/Tx) than that in parent SKOV3 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were cultured in paclitaxel‐free medium for 1 week before further studies. Episodic determinations of inhibitory concentration 50% (IC 50 ) values confirmed that paclitaxel‐resistant phenotypes were stable for at least 2 months in drug‐free medium .…”
Section: Methodsmentioning
confidence: 99%
“…A study analysing chemoresistance to the drug 3-bis (2-chloroethyl)-1-nitrosourea in malignant rat glioma cells found PPIA to be decreased in the drug resistant compared with responsive cells at the protein level 39 , confounding the results observed here. Interestingly a study analysing paclitaxel chemoresistance in the ovarian cancer cell line SKOV3 found another PPIase, FKBP5, to be transiently up-regulated 100 fold at the mRNA level whilst chemoresistance was being established in the cells 40 . Long term expression of FKBP5 however, was decreased in the resistant cells compared to the responsive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic and biological data have suggested that androgens and androgen receptor (AR) may play a role in the occurrence of ovarian cancer (3,4). The AR is a ligand-dependent transcriptional factor mediating the actions of testosterone and dihydrotesterone (5).…”
Section: Introductionmentioning
confidence: 99%
“…Mapped to X chromosome (q11. [2][3][4][5][6][7][8][9][10][11][12], the AR gene includes eight exons. In exon 1 is a trinucleotide cytosine, adenine, guanine (CAG) repeat, which encodes a polyglutamine tract with varying lengths (5).…”
Section: Introductionmentioning
confidence: 99%